Oligoclonal bands: clinical utility and interpretation cues - Carta, Sara; Ferraro, Diana; Ferrari, Sergio; Briani, Chiara; Mariotto, Sara (Critical reviews in clinical laboratory sciences, 2022)
Oligoclonal immunoglobulin G (IgG) bands (OCBs) are a useful diagnostic tool to detect a central humoral response. In particular, cerebrospinal fluid (CSF)-restricted OCBs represent a hallmark of multiple sclerosis (MS), where they can be detected in > 90% of cases and support its diagnosis, although a specific causative agent inducing B cell activation has not yet been identified. The determination of intrathecal IgM, including IgM/lipid-specific IgM OCBs, on the other hand, seems to be of prognostic relevance and is associated with a more aggressive disease course. OCBs can also be present in other central nervous system (CNS) disorders, including antibody-mediated, inflammatory, infectious, and neurodegenerative conditions, as well as in both chronic and early disease stages, suggesting the occurrence of primary or concomitant immune-mediated processes. Finally, intrathecal humoral immune response can also occur, although rarely, in patients with peripheral neuropathies, particularly in those of inflammatory origin, as a possible consequence of blood-spinal nerve root barrier (BSNRB) damage. Isoelectric focusing (IEF) on agarose gels followed by immunoblotting is the technique recommended for OCB detection, analyzing paired undiluted CSF and serum samples. However, technical issues including blot, staining, and IEF reproducibility as well as operator-dependent pattern interpretations decrease reproducibility, causing misinterpretations of results, with significant diagnostic implications. These technical issues can lead to difficulties in distinguishing between negative results (type 1 pattern = absence of OCBs in serum and CSF and type 4 pattern = presence of identical OCBs in both serum and CSF) and results indicating intrathecal IgG synthesis (pattern 2 = presence of OCBs in CSF and type 3 = presence of OCBs in CSF and additional identical OCBs in both serum and CSF). Corrective measures and identification of specialized laboratories with expertise in the field are fundamental to applying this useful technique in clinical practice. In this context, recent research has focused on the automated assessment of CSF kappa free light Ig chains as a more sensitive, non-operator-dependent marker of intrathecal Ig synthesis. We herein review central and peripheral nervous system conditions associated with OCBs and discuss their relation with pathogenetic mechanisms.